At the Roots of a Global Environmental History: An Ethiopian Loop in Nature’s Archives - (:unkn) unknown (My University, 2022)
This article reflects on the individual and collective trajectory of research on the environmental history of Africa carried out between 2008 and 2021. It first addresses the attempt to write an environmental history of the Ethiopian nation. The aim was to shed light on the history of the national shaping of nature, and to do this, the archival research was defined by a theoretical framework. Nature is a place where three types of struggles are at play: institutional (to build a territory); cultural (to promulgate a representation in the public space); and material (to exploit a resource). Therefore, the archives to be collected were those providing information on the three dimensions of this history: laws and activity reports for tracking back the stages involved in setting nature into a national park, taking the Simien Park as an example; tourist brochures and evidence of development of hiking trails, for understanding the public construction of a wild and virgin nature; reports of scientific missions for grasping the material evolution of ecologies. A second research project was then devoted to the global history of natural heritages in the South, in Africa and Asia. Here, archives determined the theory: scientific documentation produced by foresters, veterinarians, biologists, or agronomists; archives from colonial administrators, national officials, and experts employed by international conservation institutions; correspondence, life stories, and photographs relating to the management and exploration of setting nature into a park. These sources indicated that, throughout the twentieth century, in Ethiopia, Congo, Zanzibar, Seychelles, Vietnam, Cambodia, and Malaysia, Western nature professionals circulated from natural space to natural space, from country to country, and even from continent to continent. Studying traces of these circulations in the archives revealed another history and another geography of the South: those of an Afro-Asian area th
Keywords: African Research